Access to awareness of direct gaze is related to autistic traits. Issue 6 (27th June 2018) - Madipakkam, Apoorva Rajiv; Rothkirch, Marcus; Dziobek, Isabel; Sterzer, Philipp
Abstract: Background: The atypical processing of eye contact is a characteristic hallmark of autism spectrum disorder (ASD). The severity of these symptoms, however, is thought to lie on a continuum that extends into the typical population. While behavioural evidence shows that differences in social cognitive tasks in typically developed (TD) adults are related to the levels of autistic-like traits, it remains unknown whether such a relation exists for the sensitivity to direct gaze. Methods: In two experiments, we measured reaction times to detect the faces with direct and averted gaze, suppressed from awareness, i.e. the access to awareness. In experiment 1, we tested N = 19 clinically diagnosed adults with ASD and N = 22 TD matched controls, while in experiment 2, we tested an independent sample of N = 20 TD adults. Results: In line with the literature, experiment 1 showed preferential processing of direct gaze in the TD group but not in the ASD group. Importantly, we found a linear relationship in both experiments between the levels of autistic traits within the groups of TD participants and their sensitivity to direct gaze: with increasing autistic characteristics, there was a decrease in sensitivity to direct gaze. Conclusion: These results provide the first evidence that differences in gaze processing and the sensitivity to direct gaze are already present in individuals with subclinical levels of autistic traits. Furthermore, they lend support to the continuum view of the disorder and could potentially help in an earlier diagnosis of individuals at high risk for autism.